2020
DOI: 10.3389/fmicb.2020.482585
|View full text |Cite
|
Sign up to set email alerts
|

Hfq-Assisted RsmA Regulation Is Central to Pseudomonas aeruginosa Biofilm Polysaccharide PEL Expression

Abstract: To appropriately switch between sessile and motile lifestyles, bacteria control expression of biofilm-associated genes through multiple regulatory elements. In Pseudomonas aeruginosa , the post-transcriptional regulator RsmA has been implicated in the control of various genes including those related to biofilms, but much of the evidence for these links is limited to transcriptomic and phenotypic studies. RsmA binds to target mRNAs to modulate translation by affecting ribosomal access and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 98 publications
0
11
0
Order By: Relevance
“…The above results fully demonstrated that Hfq can play a pivotal role of comprehensively regulating the physiological activities of Bt. Hfq had also been shown to regulate bacterial motility ( Schachterle et al, 2019 ), biofilm formation ( Irie et al, 2020 ), and virulence in some Gram-negative bacteria ( Pearl Mizrahi et al, 2021 ), suggesting that the regulation of certain physiological activities in bacteria by Hfq is universal. However, in Bs, deletion of Hfq was found to affect relatively fewer physiological functions, such as bacterial survival ( Rochat et al, 2015 ), motility, chemotaxis ( Jagtap et al, 2016 ) and cellulolysis etc.…”
Section: Discussionmentioning
confidence: 99%
“…The above results fully demonstrated that Hfq can play a pivotal role of comprehensively regulating the physiological activities of Bt. Hfq had also been shown to regulate bacterial motility ( Schachterle et al, 2019 ), biofilm formation ( Irie et al, 2020 ), and virulence in some Gram-negative bacteria ( Pearl Mizrahi et al, 2021 ), suggesting that the regulation of certain physiological activities in bacteria by Hfq is universal. However, in Bs, deletion of Hfq was found to affect relatively fewer physiological functions, such as bacterial survival ( Rochat et al, 2015 ), motility, chemotaxis ( Jagtap et al, 2016 ) and cellulolysis etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been thoroughly characterized in T3SS + strains where it activates the T3SS. Vfr regulates its own expression through a positive feedback loop (Fuchs et al, 2010), and is under post-transcriptional regulation by the RNA-binding proteins RsmA and Hfq (Irie et al, 2020). Hfq is a regulatory protein that mainly facilitates regulation of translation via interaction with small noncoding RNAs and their mRNA targets (Vogel & Luisi, 2011).…”
Section: Signal Functionmentioning
confidence: 99%
“…Consequently, in P. aeruginosa , the Rsm system influences organism pathogenicity and patient disease state by governing the transition from acute to chronic infection ( Sonnleitner et al., 2006 ). Biofilm formation is further controlled in P. aeruginosa by the chaperone protein Hfq, which mediates the expression of RsmA protein in this network and thus indirectly controls the formation of biofilms ( Irie et al., 2020 ).…”
Section: Impacts Of Hfq-srna Regulation On Bacterial Cell Physiology and Virulencementioning
confidence: 99%